2011
DOI: 10.3390/w3010196
|View full text |Cite
|
Sign up to set email alerts
|

AnnAGNPS Model Application for Nitrogen Loading Assessment for the Future Midwest Landscape Study

Abstract: Abstract:The Future Midwest Landscape (FML) project is part of the US Environmental Protection Agency (EPA)'s new Ecosystem Services Research Program, undertaken to examine the variety of ways in which landscapes that include crop lands, conservation areas, wetlands, lakes, and streams affect human well-being. The goal of the FML project is to quantify current and future ecosystem services across the region and to examine changes expected to occur as a result of the growing demand for biofuels. This study is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The results in this study are in agreement with previous studies [11][12][13]15] that also demonstrated that implementation of best management practices could reduce increase in TP and sediment loss caused by land use Copyright © 2012 SciRes. JWARP change.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results in this study are in agreement with previous studies [11][12][13]15] that also demonstrated that implementation of best management practices could reduce increase in TP and sediment loss caused by land use Copyright © 2012 SciRes. JWARP change.…”
Section: Discussionsupporting
confidence: 92%
“…Vegetative buffers, wetlands and management of fertilizer and manure have been suggested by prior studies to be more effective in reducing sediment and P loss into streams [11,12]. In addition, crop rotation (for instance corn-soybean instead of continuous corn) is known to reduce sediment, nutrient and pesticide loss [13]. Soybean has the ability to fix N and requires low amounts of P fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn led to a surge of total U.S. planted corn acreage (USDA-NASS, 2007), which remained high relative to long-term historical pattern (USDA-NASS, 2010) and would be close to 36 million hectares for the coming decade (USDA-ERS, 2010). The increase in planted corn acreage which requires high fertilizer application rate is projected to further exacerbate water quality problems within the URMB, the larger Mississippi River watershed, and the Gulf of Mexico (Simpson et al, 2008;Donner and Kucharik, 2008;Secchi et al, 2010;Yuan et al, 2011). Over past years, a variety of conventional best management practices (BMPs) such as riparian buffers, filter strips, and grassed waterways have been employed to reduce nutrient and sediment losses (Osborne and Kovacic, 1993;Mitsch et al, 2001;Syversen, 2005;Sahu and Gu, 2009;USDA-NRCS, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Agricultural lands that have cornesoybean rotation and "soybean_other" were associated with reduction in TSS and TP. Soybean and other leguminous crops improve soil conditions and fixes nutrients required by corn (Yuan et al, 2011). It is a conservation method that reduces TSS and TP loadings to streams because of reduction in fertilizer and tillage needs.…”
Section: Pls Resultsmentioning
confidence: 99%